Withholding Tax System of Income Tax Article 4 Paragraph (2) on Lottery Prizes and Savings Interest at PT Bank SulutGo - Sitompul, Zefanya Yohana; Rondonuwu, Sintje; Suwetja3, I Gede (Formosa Journal of Applied Sciences, 2024)
In the current year, collection and self-remittance, and withholding are several ways of paying taxes. Article 4 paragraph (2) of Income Tax is a final tax. This study aims to determine the ways in which the tax revenue reduction system of article 4 paragraph (2) of PT Bank SulutGo applies to savings interest and lottery winnings. The main data source of this qualitative research is employee interviews at PT Bank SulutGo. Based on the research findings, 25% of lottery winnings are subject to income tax based on Article 4 paragraph (2) in accordance with PP No. 132 Year 200, and 20% of savings interest is subject to income tax based on PT Bank SulutGo's tax deposit and reporting has been in accordance with PMK Number 242 Year 2014, and Article 4 paragraph (2) in accordance with PP Number 123 Year 2015.